Kondisi Sosial Ekonomi Keluarga Petani Terdampak Alih Fungsi Lahan Sawah di Lima Puluh Kota - Dzikri, Dwi Rahmat (Universitas Merdeka Malang, 2024)
This research explains the transfer of land functions that have an impact on the social and economic condition of farming families that occur in the Nagari Guguak VIII Koto, Kecamatan Guguak, Kabupaten Lima Puluh Kota. The problem in this study is how the form of changes in the socio-economic life of the farming family of farmers after the phenomenon of land transfer and what is the strategy carried out by cultivator farmers as an effort to fulfill needs after the transfer of the function of rice fields. This research uses a qualitative method that is descriptive, and with data collection techniques such as interview, observation, and documentation while at the research site. As for the selection of informants using purposive sampling, namely with key informants as many as six cultivator farmers and three landowners. The results show that with the transfer of function of rice fields has a very significant impact on the social and economic life of the farming family which depends on the results of working on rice fields. The phenomenon of land transfer decrease the economics of the farmers, so that they were required to seek other innovations in order to meet their needs such as breeding and so on.